Semen Quality and Kinematics of Swamp Buffalo Sperm Diluted with Different Extenders - Andriani, Desi; Hendri, Hendri; Masrizal, Masrizal (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This study aims to identify the best extender that can maintain the quality of swamp buffalo semen at UPTD BPTSD Tuah Sakato. This study used 1 swamp buffalo bull located at UPTD BPTSD Tuah Sakato. This study used a Completely Randomized Design (CRD) consisting of 4 treatments and 6 replications, the treatments given were differences in diluent materials including P1 (Tris Egg Yolk), P2 (Steridyl), P3 (Bioxcell), and P4 (Optixcell). The variables observed in this study included the quality of fresh semen, frozen semen, and spermatozoa kinematics. The research data were analyzed by ANOVA and DMRT further test using the IBM SPSS v.25 application. The findings of this study indicate that differences in diluent materials have a significant effect (P <0.05) on the motility and abnormality of swamp buffalo semen, but do not have a significant effect (P> 0.05) on the viability, MPU, and TAU of swamp buffalo spermatozoa. The difference in diluent materials gave a significant effect (P<0.05) on ALH of swamp buffalo sperm, but did not have a significant effect (P>0.05) on VAP, VCL, VSL, STR, LIN, and BCF of swamp buffalo sperm. Based on the results of this study, it was found that egg yolk tris is the best extender that can maintain the quality of swamp buffalo semen both in terms of frozen semen quality and spermatozoa kinematics.